Geodynamic development of the Ingul megablock of the Ukrainian Shield for geological-geophysical and tectonophysical data. I - O.B. Gintov; S. V. Mychak (Геофизический журнал, 2011)
The article presents the data based on the materials of the 25-year tectonophysical study of the central part of the Ukrainian Shield. The purpose of the article is to show that the geodynamic evolution of the Shield since at least the late Archean was subordinated to the mechanisms of plate tectonics. The main arguments are: a decisive role in shaping the structure of the Precambrian basement of large sub-horizontal shifts along the wide shear zones, with initial stage in the Early Precambrian; the passing of the deformation processes in the formation of most fracture and folded structures in the subhorizontal position of the plane of the principal axes of the normal stresses Oj, O3; the establishment of zones of listric type and large gently dipping thrusts in the lithosphere of the shield; radical difference in the geodynamic evolution of the Archean western and eastern parts of the shield in case of the absence of the zone with the transitional deformation regime. In the first part of this article the general situation of the Ingul megablock in the structure of the Ukrainian Shield has been discussed and its borders were grounded. A scheme of the geological structure and structural tectonophysical map of the megablock have been given here. The concepts of the "fault zones" and "zones of cleavage" as well as the "stage" and the "phase" of deformation (faulting) have been discussed. 13 stages of deformation within the megablock covering the time from the Neo-Archean to Neo Proterozoic and having a decisive influence on the formation of its inner structure were described.